Photochemistry upon Charge Separation in Triphenylamine Derivatives from fs to μs - Brockmann, Hendrik J.; Huang, Letao; Hainer, Felix; Galindo, Danyellen; Jocic, Angelina; Han, Jie; Kivala, Milan; Dreuw, Andreas; Buckup, Tiago (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2025)
Quantum chemical methods and time-resolved laser spectroscopy are employed to elucidate ultrafast charge-separation processes in triphenylamine (TPA) derivatives upon photoexcitation. When changing the ambient solvent from non-electron-accepting to electron-acceptor solvents, such as chloroform, a vastly extended and multifaceted photochemistry of TPA derivatives is observed. Following initial excitation, two concurrent charge-transfer processes are identified. When the TPA derivative and solvent molecules are arranged in a configuration that favors efficient electron transfer, charge separation occurs immediately, leading to the formation of a radical cation of the TPA derivative. This highly reactive species can subsequently combine with other TPA derivative molecules to yield a dimeric species. Alternatively, if the molecular positioning upon photoexcitation is not optimal, relaxation back to the S1 state occurs. From this state, an electron transfer process leads to the formation of a charge-transfer complex, where the negatively charged solvent molecule remains closely associated with the positively charged TPA derivative. Within 30 ps, charge recombination occurs in this complex, resulting in the formation of triplet states. This transition to the triplet state is driven by a lower reaction barrier for charge separation compared to that for the formation of the singlet state.